Keeping it Together: Assessing the Wellbeing of Project-Based Development Practitioners in Egypt - Ahmed Abdallah Fekry Ahmed, Amira (AUC Knowledge Fountain, 2026)
This thesis examines the wellbeing of project-based development practitioners in Egypt, revealing how systemic pressures—bureaucracy, job insecurity, and fragmented workloads—undermine both wellbeing and productivity. The study employed a mixed-approach, combining 10 in-depth interviews with subject matter experts and practitioners and 75 surveys with development practitioners in Egypt. Data revealed that while many practitioners are driven by purpose, structural challenges erode resilience and motivation over time. Social support networks and personal coping strategies help but cannot replace institutional protections. The study argues that wellbeing must shift from being treated as an individual concern to a structural responsibility. Reframing organizational models around human-centered logic and community resilience is essential. Safeguarding practitioner wellbeing is not just ethical—it is key to sustaining effective development work.